Tender Evaluation Process and Operational Performance of Service State Corporations in Kenya. - Obura, Collins Ochieng; Shale, Noor Ismail; Mukanzi, Clive Mukanzi (International Journal of Supply Chain and Logistics, 2023)
Purpose: Service State corporations are incorporated entities outside the mainstream civil service established for purposes of public service delivery. Performance of the state agencies is constantly under public scrutiny, in part because much of the funding and equity in them flows directly from the tax base of the Country. However, public procurement process has not matched the expectation of stakeholders in terms of achieving value for money and budget execution. This study therefore, sought to determine the influence of tender evaluation process on operational performance of service state corporations in Kenya. Methodology: This study adopted a survey research design. The study focused on the audit, ICT and Procurement Managers respectively as respondents of the 132 service state corporations in Kenya. Stratified Sampling Design was employed since the study population is not homogenous. Data was collected using self-administered questionnaires. The data collected was analyzed using SSPS version 21. Data analysis was conducted using descriptive and inferential statistics by use of moderated multiple regression analysis. Findings: The findings of this study revealed that tender evaluation process had a significant and positive influence on operational performance of service state corporations in Kenya. The model result found out that the coefficient of determination was 0.424 implying that 42.4% of operational performance of service state corporations in Kenya is explained by tender evaluation process. The study concluded that tender evaluation process was critical in enhancing the performance of service state corporations in Kenya. Unique contribution to theory, practice and policy: The study recommended that, in order to achieve value for money and reduce on cost of acquisition, service state corporations must implement the e-tendering process and adopt a transparent ranking procedure during the Tender evaluation Process. This will discourage against the deliberate use of fake competition by favoring a particular bidder. In addition, procurement purchases should be based on the prevailing market trends and consider the total cost of ownership.